LANGUAGE, POWER, AND CLASS: EXPLORING UNEQUAL DISTRIBUTION OF LINGUISTIC CAPITAL IN THOMAS HARDY’S TESS OF THE D’URBERVILLES (Contemporary Journal of Social Science Review, 2025)
This study uses Pierre Bourdieu's sociological theory to analyse the unequal distribution of linguistic capital in Thomas Hardy's Tess of the d'Urbervilles (1891). By using a qualitative textual analysis methodology, the study explores how language reinforces class and gender hierarchies in Victorian England by serving as a vehicle of social stratification. The study focusses on the speech patterns, dialects, and access to "legitimate" language of the characters, exposing glaring differences: Tess Durbeyfield's rustic accent identifies her as socially marginalised, while characters like Angel Clare and Alec d'Urberville employ standard English to establish dominance. Tess continues to be linguistically disempowered despite her efforts to speak more elegantly, which is indicative of structural obstacles to social mobility. In addition to examining instances of resistance through Tess's quiet agency and the novel's sympathetic narrative voice, the research emphasises Hardy's criticism of Victorian society systems, particularly the moral hypocrisy and inflexible class system. Results highlight language's symbolic importance as a tool for subtly resisting injustice. This study adds a new sociolinguistic dimension to the body of literary criticism on Hardy's work by fusing feminist and sociolinguistic viewpoints with Bourdieu's theory. It highlights the ways in which class, gender, and linguistic capital intersect to shape opportunity and identity. In order to better understand the nuances of linguistic inequality in literature and culture, the study ends with recommendations for future research that emphasise multidisciplinary approaches.